2017
DOI: 10.1177/0267659117701562
|View full text |Cite
|
Sign up to set email alerts
|

Volatile anaesthetics added to cardiopulmonary bypass are associated with reduced cardiac troponin

Abstract: Adding volatile anaesthetics during cardiopulmonary bypass was associated with reduced peak postoperative troponin levels. Larger studies are required to confirm our data and to assess the effect of volatile agents on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Several clinical studies and meta-analyses have demonstrated the contribution of a potential cardioprotective strategy by sevoflurane postconditioning. 17,22,23,40 Related fundamental research assumed the involvement of the protein kinase C, PI3K/Akt, and extracellular signal-related kinase 1/2 pathways. 23 The safety and efficacy of DEX in perioperative cardiac surgery have been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies and meta-analyses have demonstrated the contribution of a potential cardioprotective strategy by sevoflurane postconditioning. 17,22,23,40 Related fundamental research assumed the involvement of the protein kinase C, PI3K/Akt, and extracellular signal-related kinase 1/2 pathways. 23 The safety and efficacy of DEX in perioperative cardiac surgery have been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anaesthetics such as sevoflurane play a significant role in improving outcomes by decreasing the oxygen demand. 25 Methylprednisolone and mannitol may be used to improve brain oedema. 26 Overall, our experience revealed that unilateral EC is sufficiently safe, which is consistent with the findings of some prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…1 reduction in mortality led to an increase in their use during CPB, since their cardioprotective properties might be related to the administration modalities. [2][3][4][5] Other benefits of using this technique are the reduction of CPB-induced inflammatory response, of the systemic vascular resistance and the improvement in cerebral oxygen saturation. [6][7][8] The use of VAA during CPB requires special precautions like connecting exhaust systems to the oxygenator's gas outlet port, which are mandatory to prevent operating room (OR) pollution.…”
Section: Introductionmentioning
confidence: 99%